Ketogenic Metabolic Therapy, Without Chemo or Radiation, for the Long-Term Management of IDH1-Mutant Glioblastoma: An 80-Month Follow-Up Case Report - Seyfried, Thomas N.; Shivane, Aditya G.; Kalamian, Miriam; Maroon, Joseph C.; Mukherjee, Purna; Zuccoli, Giulio (Frontiers in Nutrition, 2021)
Abstract Background Successful treatment of glioblastoma (GBM) remains futile despite decades of intense research. GBM is similar to most other malignant cancers in requiring glucose and glutamine for growth, regardless of histological or genetic heterogeneity. Ketogenic metabolic therapy (KMT) is a non-toxic nutritional intervention for cancer management. We report the case of a 32-year-old man who presented in 2014 with seizures and a right frontal lobe tumour on MRI. The tumour cells were immunoreactive with antibodies to the IDH1 (R132H) mutation, P53 (patchy), MIB-1 index (4-6%), and absent ATRX protein expression. DNA analysis showed no evidence of methylation of the MGMT gene promoter. The presence of prominent microvascular proliferation and areas of necrosis were consistent with an IDH-mutant glioblastoma (WHO Grade 4). Methods The patient refused standard of care (SOC) and steroid medication after initial diagnosis but was knowledgeable and self-motivated enough to consume a low-carbohydrate ketogenic diet consisting mostly of saturated fats, minimal vegetables, and a variety of meats. The patient used the glucose index calculator to maintain his Glucose Ketone Index (GKI) near 2.0 without body weight loss. Results The tumour continued to grow slowly without expected vasogenic edema until 2017, when the patient opted for surgical debulking. The enhancing area, centered in the inferior frontal gyrus, was surgically excised. The pathology specimen confirmed IDH1-mutant GBM. Following surgery, the patient continued with a self-administered ketogenic diet to maintain low GKI values, indicative of therapeutic ketosis. At the time of this report (April 2021), the patient remains alive with a good quality of life, except for occasional seizures. MRI continues to show slow interval progression of the tumour. Conclusion This is the first report of confirmed IDH1-mutant GBM treated with KMT and surgical debulking without chemo- or radiotherapy. The long-term survival of this patient, now at 79 months, could be due in part to a therapeutic metabolic synergy between KMT and the IDH1 mutation that simultaneously targets the glycolysis and glutaminolysis pathways. Further studies are needed to determine if this non-toxic therapeutic strategy could be effective in providing long-term management for other GBM patients with or without IDH mutations.